Hybrid electrochemical supercapacitors based on aqueous electrolyte solutions - Bakhmatyuk, B.P.; Kurepa, A.S. (Физическая инженерия поверхности, 2012)
In this paper it was investigated the system of the hybrid iodine electrochemical supercapacitor,
which provides the discharge capacity over 7500 F/g. Microporous carbon material obtained by high
temperature steam activation of the natural raw materials was used as an anode material for electrodes
preparation. Moreover, the system of hybrid alkaline electrochemical supercapacitor was investigated,
and it was proved, that additional activation of the activated carbon material in the molten NaOH can
increase the available for charge surface of the material. As a result, discharge capacity per weight
of active material can increase up to 342 F/g and the energy density is 6.5 times greater than value of
known symmetric supercapacitors. Вроботі використовуючи мікропористий вуглецевий матеріал, отриманий високотемпературною
активацією у водяній парі природньої сировини, досліджена система йодидного гібридного електрохімічного суперконденсатора, що забезпечує питому ємність на розряді понад 7500 Ф/г. Досліджена система лужного гібридного електрохімічного суперконденсатора і доведено, що доактивація активованого вуглецевого матеріалу в розплаві NaOH дозволяє підвищити доступну
до заряду поверхню матеріалу. І як результат дозволяє підвищити розрядну ємність на масу
активного матеріалу до 342 Ф/г та збільшує питому енергоємність в 6,5 разів у порівнянніз відомими симетричними суперконденсаторами. В работе используя микропористый углеродный материал, полученный высокотемпературной
активацией в водяном паре естественного сырья, исследована система йодидного гибридного
электрохимического суперконденсатора, которая обеспечивает удельную емкость на разряде
свыше 7500 Ф/г. Исследована система щелочного гибридного электрохимического суперконденсатора и доказано, что дополнительная активация активированного углеродного материала в
расплаве NaOH, позволяет повысить доступную для заряда поверхность материала. И как
результат позволяет повысить разрядную емкость на массу активного материала до 342 Ф/г и
увеличивает удельную энергоемкость в 6,5 раз по сравнению с известными симметричными
суперконденсаторами.